Neuropharmacological profile of Hypericum scabrum L. essential oil in rats - Sur, Tariq Mohammed; Akbaba, Emel; Hassan, Salam A.; Bagci, Eyup (Taylor & Francis Inc, 2020)
Members of the genus Hypericum L. are traditionally used for various illnesses including depression. In this study, the effects of essential oil obtained from Hypericum scabrum L. on anxiety and depressive-like behavior were evaluated in dementia animal model. H. scabrum essential oil (1% and 3%) was applied to rats for 21 days by inhalation. Then, the rats were treated with scopolamine prior to behavioral tests: elevated plus maze and forced swimming test. H. scabrum essential oil increased the number of open arm entries and number of crossings within elevated plus maze as compared to scopolamine-alone treated group, demonstrating anxiolytic effect. Furthermore, depressive-like symptoms induced by scopolamine were reduced by H. scabrum essential oil inhalation as evidenced by increases in the swimming time and decreases in the immobility time within forced swimming test. These results show anxiolytic and antidepressant-like activities of H. scabrum essential oil in dementia rat model.
Keywords: Hypericum scabrum essential oil; alpha-pinene; scopolamine; anxiety; depression